Intraoperative Seizures Detected as Increased Bispectral Index Values during Posterior Fossa Surgeries - Srinivas, Deepti; Radhakrishnan, Muthuchellappan; Chakrabarti, Dhritiman; Lakshmegowda, Manjunatha; Manohar, Nitin (Journal of Neuroanaesthesiology and Critical Care, 2018)
We present a case series of four cerebellopontine angle surgeries with intraoperative detection seizure activity. The cases discussed follow the uniform anesthetic protocol of maintenance with infusion of propofol, fentanyl and dexmedetomidine excluding muscle relaxant, targeted to maintain bispectral index (BIS) in the range of 40 to 60. The cases experienced either of the two scenarios: (I) Unexplained increased or widely varying BIS values associated with increases in BIS electromyography (EMG) and motor manifestation of seizure activity in limbs. (2) Varying BIS values with EMG activation of facial nerve monitoring without motor manifestation in limbs. A common theme noticed in all these cases was the utilisation of tranexamic acid in cumulative doses of 25 to 30 mg/kg and amelioration of the seizure activity with a loading dose of phenytoin (15 mg/kg). A hypothesis is being presented linking intraoperative seizures with a combination of tranexamic acid utilisation.
Keywords: intraoperative seizures; posterior fossa surgery; tranexamic acid